Estimating the Employment and GDP Multiplier of Emergency Cash Transfers in Brazil - Cunha, Daniel; Accioly Perrelli, Roberto; Pereira, Joana; Toscani, Frederik (Washington, D.C. : International Monetary Fund, 2022)
We estimate the subnational employment and GDP multiplier of Brazil's 2020 federal cash transfers to vulnerable households. Using two-stage least squares regressions we estimate a formal employment multiplier and then apply an analytical transformation to recover an implied GDP multiplier in the range of 0.5-1.5. The lower bound of this range lies below most estimates in the literature, which may result from the exceptional constraints imposed by the pandemic on supply chains and consumption. Nevertheless, even using the lower end of our range implies that federal cash transfers played an important role in supporting employment and GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Finance in Urban and Rural Economies; Fiscal Multipliers, Household Cash Transfers and Labor Informality; Fiscal Policy; National Government Expenditures and Welfare Programs